The Polish Thought in the Russian-speaking Zone - Skoczyński, Jan (Folia Philosophica, 2018)
This paper refers to the Russians’ and Belarusians’ interests of the Polish philosophical and social thought of the 19th and 20th centuries. The Polish thought — in the wide understanding of this notion — despite the political difficulties, it is known and commented behind the eastern Polish border. Seldom the Polish thought is a point of reference for building their own intellectual self-knowledge.Art